Escherichia coli in Food and Hands of Handlers in Catering service Group A1 and A2 - Windi Wulandari; Zulia Setiyaningrum; Sunarto Sunarto; Acintya Wedaning Agni Janametri; Shesa Ratna Suryaning Putri (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Food hygiene was a controlling factor for food contamination that can cause foodborne diseases such as diphtheria, diarrhea, typhoid, and food poisoning. Several types of microbes that can cause food poisoning, one of which is Escherichia Coli. The purpose of this study was to analyze the relationship between personal hygiene, food hygiene, sanitation facilities, with Escherichia Coli food and hands of handlers in catering services of groups A1 and A2. This research method uses Cross Sectional study, sampling techniques in research using Accidental Sampling in catering service groups A1 and A2 in the Banyudono District. This research was carried out from May to June 2022, the research location was in catering service in the Banyudono district area. This sample in this study was 25 food handlers.The data analysis was done by Chi Square test. The results showed that the handlers had good personal hygiene by 52%, good food hygiene 72%, inadequate sanitation facilities 52%, Escherichia coli in food 56%, and Escherichia coli in hands 84%. There was no relationship between personal hygiene (p-value = 0.302) and food hygiene (p-value = 0.177) with the content of Escherichia coli in food. There was a relationship between sanitation facilities (p-value = 0.000) and the content of Escherichia coli in food. There was no relationship between personal hygiene (p-value = 0.096), food hygiene (p-value = 0.548) and sanitation facilities (p-value = 0.322) with Escherichia Coli on hands. Food service handlers already have personal hygiene and apply good food hygiene, but Escherichia coli is still found in the food and handlers hands. Sanitation facilities still do not meet the requirements, so it is necessary to utilize available sanitation facilities to reduce Escherichia coli contamination. Keyword: Personal hygiene, Hygiene, Sanitation, Escherichia coli